Agamben and the poetics of indifference. Issue 4 (2nd October 2017) - Watkin, William
Abstract: Agamben's overall method as detailed in The Signature of All Things is named by him as philosophical archaeology. Said archaeology addresses the large-scale concepts that organise discursive structures over time and place and reveals their common metaphysical basis. In particular an impossible to sustain economy between a founding common and a founded proper which constantly change place so that the clear distinction between that which founds and that which is founded becomes impossible to discern. It becomes, in his terminology, indifferent. The signatures of Power, Life, Potentiality and Language are well known in Agamben's work, as is his love for poetry. What has not yet been commented on is that for Agamben Poetry is a signature and so must be subject to the same method of suspensive indifference as the more nefarious discourses of power and domination. In this article the signature of Poetry is defined as the economy between the semantic, or prose as founding common, and the semiotic, or poetry as founded proper. That Agamben gives so much attention to the signature Poetry is because it is central to the suspension of the basis of all signatory constructs, Language as pure communicability as such. Yet more than this Agamben's indifferentiation of poetry in terms of the perceived tension between semantic and semiotic, opens up complex and powerful forces at the heart of the poetic.